Studies on Biodiesel Synthesis Using Nanosilica Immobilised Lipase in Inverse Fluidized Bed Bioreactors - Narayanan, C. M.; Pandey, Aditi (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Biodiesel synthesis from neem oil and methyl acetate using lipase catalyst immobilised in nanosilica particles in a continuous inverse fluidised bed bioreactor of modified design has been analysed. The process has been simulated mathematically by developing a multiparameter software package and subsequently verified through pilot plant tests(experiments).The improved performance characteristics of the bioreactor of proposed design have been highlighted. Graphical data have been presented to illustrate the dependence of reactor performance on system/operating parameters such as substrate flow rate, catalyst loading and molar ratio of oil to acetate in the blend(substrate solution).The downflow mode of operation is an added advantage of these bioreactors which tends to reduce their operating cost. Due to the use of nanoparticles, the effectiveness factor is close to unity and consequently, the global rate of transesterification is more or less equal to the intrinsic rate. This enhances the performance efficiency of the bioreactor.